Field saturation and education-occupation mismatch in Vietnam - Vu, Ngoc Thi Bich; Nasar, Asim; Tran, Tuyen Quang; Dinh, Huong Thu Thi (Asian Development Policy Review, 2025)
This study measures field saturation and education-occupation mismatch in Vietnam's labor market, a country with a transitional economy. Using data from the 2018 Labour Force Survey, the study employs both the Job Analysis (JA) and Direct Self-Assessment (DSA) methods to measure education-occupation mismatch. A logistic regression model is applied to identify factors influencing mismatch, including provincial-level field saturation. The results reveal that the highest level of field saturation occurs among graduates in pedagogy and educational sciences. Saturation levels are generally lower for individuals with vocational training but significantly higher within the public sector. The econometric analysis indicates that living in provinces with greater field saturation increases the likelihood of job mismatch. Based on the JA method, the mismatch probability is higher for all other fields compared to pedagogy, except for social sciences, business, and law. The DSA method confirms similar patterns, with an exception for the health and welfare field. Field saturation contributes significantly to education-occupation mismatch in Vietnam’s labor market, particularly in the public sector and highly saturated fields. Policies should prioritize improving labor market transparency, offering stronger incentives for proactive job search behaviors, and expanding on-the-job training to bridge skill gaps.